Stock Option Rights In Transportation Company Merger And Acquisition Transactions - Ahmad Sudiro (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Merger and acquisition transactions are corporate transactions that often occur. The seller asks for an option to be able to buy back the shares of the company that are sold. The buyer asks for an option to be able to buy the remaining shares to become the majority holder. The agreement on the option rights is separated from the master sale and purchase agreement for the company's shares. This study discusses the use of share sale options in corporate mergers and acquisitions transactions. This study uses a normative judicial method. This study concludes that option rights have implications for the company and other shareholders. So that the sale or purchase option rights must be submitted to the public since the option rights arise. The option to sell and the right to buy the shares are clearly defined including the validity period, number of shares, estimated price and share ownership portion. This right has an impact on the performance of the company and interested parties. Cancellation of rights must also be communicated openly to interested parties. The agreement regarding option rights is an integral part of the main agreement